Towards a monophyletic classification of Lejeuneaceae I: subtribe Leptolejeuneinae subtr. nov. - Heinrichs, Jochen; Schäfer-Verwimp, Alfons; Czumay, Aleksandra; Dong, Shanshan; Scheben, Armin; Feldberg, Kathrin; Schneider, Harald (Phytotaxa, 2014)
We employed sequences of two chloroplast regions (trnL-trnF, rbcL) and the nuclear ribosomal ITS region of seven accessions of Leptolejeunea to explore its phylogenetic position. Maximum parsimony and maximum likelihood analyses led to similar topologies but deeper nodes received good bootstrap support only with maximum likelihood methods. Leptolejeunea formed an early diverging, robust monophyletic lineage within Lejeuneaceae tribe Lejeuneeae. Contrary to earlier belief, it is not closely related to Drepanolejeunea. To amend the current classification of Lejeuneeae into subtribes, we propose Leptolejeuneinae, subtr. nov.